Total temporomandibular joint replacement without a submandibular incision - Kim Samuel Seung Yeol; Somers Miles (Journal of Oral Medicine and Oral Surgery, 2020)
Temporomandibular joint replacement is a well-accepted and successful treatment option for advanced pathology of the temporomandibular joint. There are however a number of complications associated with the procedure such as post-operative infection, facial nerve damage and scarring. Total joint replacement has traditionally involved the use of both a pre-auricular and submandibular incision. We present an approach that uses only a pre-auricular incision without the need for a submandibular incision. This approach is less invasive and has the potential to decrease risk of damage to the marginal mandibular branch of facial nerve and scarring of the neck.